Analisis Pergeseran Struktur Ekonomi dan Sektor Unggulan di Kabupaten Tabanan Provinsi Bali - Mardiana, I Wayan; Sri Budhi, Made Kembar; Swara, I Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 3, Maret 2017 (pp. 286-471), 2017)
Leading sectors and shift of economic structure in regions having an important role in regional development .The knew sectors and shift of economic structure, be able to more maximize regional development. The research is quantitative with descriptive research, done in Tabanan Regency. The data used was primary and secondary data. Shift of economic structure has happened in Tabanan Regency, seen from small contributions the agricultural sector than the other service sector and the industrial sector. The leading sectors should be developed in Tabanan Regency is the construction sector, the health services and social activities sector, mining and quarrying sector, real estate sector, the other services sector, information and communication sector and sector administration, defense and social security must.
Keywords: Pergeseran Struktur Ekonomi; Sektor Unggulan